Efektifitas Pengembangan Bahan Ajar Mikrobiologi Berbasis Inkuiry dalam Meningkatkan Hasil Belajar Mahasiswa IKIP Budi Utomo Malang - Purwaning Budi Lestari; Triasih Wahyu Hartati (Universitas Sebelas Maret, 2017)
Higher education is expected to develop science and technology to produce intellectuals, scientists andprofessionals who are cultured and creative. Efforts made by universities through improving the quality oflearning among others with the fulfillment of development of teaching materials. The purpose of research todetermine the effectiveness of microbiology-based teaching materials development inkuiry in improvingstudent learning outcomes IKIP Budi Utomo Malang. The development research used refers to the 4Ddevelopment model of Thiagarajan (1974) with the steps, ie define, design, develop, and disseminate. Indissiminate stage done through quasi experiment. The pretest value was tested using t-test while the differencebetween pretest and postes in the test class was analyzed using the General Linear Model (GLM) MultivariateSPSS 16 program. The results showed a difference in mean of learning outcomes from the control class of19,000 and 24,114 in the treatment class . In the experimental test it is known that there is a significantdifference between the treatment class and the control class with the significant level showing 0.000. Theconclusion in this research is the development of microbiology-based materials inkuiry effective in improvingstudent learning outcomes IKIP Budi Utomo Malang.